2016
DOI: 10.1007/s11739-016-1414-x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative coagulation assessment of patients undergoing major elective orthopedic surgery

Abstract: Traditional coagulative parameters are of limited use in identifying perioperative coagulopathy occurring in patients undergoing major elective orthopedic surgery (MEOS). The aim of our study was to evaluate the coagulation changes in patients undergoing MEOS and to facilitate an early detection of perioperative coagulopathy in patients experiencing major intraoperative bleeding. We enrolled 40 consecutive patients (M/F 10/30, age range 34-90 years) who underwent MEOS at the Orthopedic Unit of the Padua Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…Another interesting result of our study is the association of reduced intrinsic pathway maximal clot firmness (MCFin) and increased extrinsic pathway clot formation time (CFT ex ) with ECMO-associated bleeding (Fig 2). These parameters reflect the functional activity of platelets, fibrinogen, fibrin stabilizing factor XIII and von Willebrand factor [27,31,33]. Taking into account normal or increased levels of fibrinogen, it can be concluded that diminished platelet hemostasis and/or FXIII dysfunction and/or acquired von Willebrand syndrome is a likely mechanism of ECMO-associated hemorrhagic complications.…”
Section: Plos Onementioning
confidence: 99%
“…Another interesting result of our study is the association of reduced intrinsic pathway maximal clot firmness (MCFin) and increased extrinsic pathway clot formation time (CFT ex ) with ECMO-associated bleeding (Fig 2). These parameters reflect the functional activity of platelets, fibrinogen, fibrin stabilizing factor XIII and von Willebrand factor [27,31,33]. Taking into account normal or increased levels of fibrinogen, it can be concluded that diminished platelet hemostasis and/or FXIII dysfunction and/or acquired von Willebrand syndrome is a likely mechanism of ECMO-associated hemorrhagic complications.…”
Section: Plos Onementioning
confidence: 99%
“…Spiezia et al reported that patients with a reduced FIBTEM MCF had excessive bleeding, and recommended that thromboelastometry be one of the routine preoperative coagulation tests in patients undergoing major orthopedic surgery. 10 Görlinger et al found that FIBTEM A10 correlated with FIBTEM MCF and concluded that early FIBTEM would be useful for managing hemorrhagic patients undergoing noncardiac surgery. 11 The preoperative FIBTEM A10 was strongly correlated with the preoperative FIBTEM MCF in this study (ρ ¼ 0.990, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 A few studies have suggested that intraoperative thromboelastometry could be a guide for hemostatic therapy in patients undergoing noncardiac surgery, including major orthopedic surgery. 10,11 Early thromboelastometry-guided transfusion therapy reduces the amount of transfusion and hemorrhage-related morbidity and mortality. [12][13][14] Recently, Na et al found that the FIBTEM maximum…”
mentioning
confidence: 99%
“…The use of ROTEM to guide therapy has been described in multiple clinical settings including trauma, obstetrical hemorrhage, cardiac surgery, orthopedic surgery, and craniosynostosis surgery . The benefit of viscoelastic testing is that this assay accounts for the contribution of platelets and fibrinogen to clot formation and, therefore, is expected to better predict in vivo coagulation status than traditional laboratory testing.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The use of ROTEM to guide therapy has been described in multiple clinical settings including trauma, obstetrical hemorrhage, cardiac surgery, orthopedic surgery, and craniosynostosis surgery. [5][6][7][8][9] The benefit of viscoelastic testing is that this assay accounts for the contribution of platelets and fibrinogen to clot formation and, therefore, is expected to better predict in vivo coagulation status than Abstract Introduction: Rotational thromboelastometry (ROTEM) is increasingly used as a tool for monitoring coagulation status. However, ROTEM is susceptible to misinterpretation due to particular coagulation abnormalities.…”
mentioning
confidence: 99%